As práticas de sociabilidades dos grupos dirigentes na cidade de Natal: os clubes como marcadores de distinções sociais (1920-1929) - Lopes, Karine Maria Lima (2021)
The leading groups in the city of Natal, in the early decades of the twentieth century, led an intense process of material transformations, such as the reconstruction of the Tavares de Lyra pier, the construction of the Carlos Gomes Theater and the introduction of electricity and electric trams. From the 1920s onwards, this modernization process intensified with the administration of Mayor Omar O'Grady (1924-1930), and its peak occurred with the elaboration of the General Systematization Plan (Palumbo Plan), in 1929, which aimed to model the city and plan its growth based on the precepts of urbanism and hygiene. The changes that were taking place were aimed at meeting the aspirations of the leading groups to transform Natal into a modern city, whose development would be guided by progress. These groups created new institutions and established their social spaces according to their wishes and values. They promoted, from the 1920s, the appearance of exclusive environments for social interaction, among which we will emphasize the aero club and sports clubs, specifically rowing competitions. We will try to show that the dominant groups sought to transform them into educational places, extolling the principles of wholesomeness, beauty and order. We will accompany the forms of socialization mentioned through the periodicals that celebrated the changes in the social dynamics of the capital of Rio Grande do Norte. The newspaper “A Republica” provided us with elements of analysis on the statutes and principles that regulated the access of individuals to sports associations and recreational clubs. The magazine “Cigarra”, which circulated in the capital between 1928 and 1930, brought up photographs of the time, texts by memorialists and news about individuals of social importance in the mainstream press. Therefore, this work aims to understand the sociability practices of the urban upper classes and assist us in the perception of the desires and tensions of the modern city intended by the dominant groups.